Vitamin D: A New Perspective in Treatment of Cerebral Vasospasm After Subarachnoid Hemorrhage. (1st September 2019) - Kashefiolasl, Sepide; Leisegang, Matthias; Helfinger, Valeska; Schürmann, Christoph; Pflüger-Müller, Beatrice; Randriamboavonjy, Voahanginirina; Vasconez, Andrea Estefy; Carmeliet, Geert; Badenhoop, Klaus; Hintereder, Gudrun; Seifert, Volker; Schröder, Katrin; et al.
Abstract: INTRODUCTION: Cerebral vasospasm (CVS) is a severe complication after subarachnoid hemorrhage (SAH). We explored vitamin D (VitD) as a possible therapeutic option for CVS. METHODS: Between 2007 and 2015, 25-vitaminD3 (VitD3) levels and data of SAH patients admitted during the months with a peak vs nadir of VitD3-values were analyzed, retrospectively. Furthermore, VitD3 and vasospasm/outcome data in SAH patients admitted in 2017 were correlated prospectively. A mice SAH model and cell culture studies were used to determine the involved mechanisms of 1, 25-dihydroxy-vitaminD3. RESULTS: A significant lower vasospasm rate and improved outcome in SAH patients admitted in summer as compared to winter time was identified by the retrospective analysis. In the SAH mouse model, active 1, 25-VitD3 attenuated CVS development, as determined by vessel diameter of basilar artery (BA) and reduced neurological deficit. 1, 25-VitD3 attenuated the inflammation of the BA in response to blood. Deletion of the myeloid or endothelial VitD-receptor decreased the protective 1, 25-VitD3 effect. Co-culture of myeloid and endothelial cells with blood confirmed the anti-inflammatory effect of 1, 25-VitD3 and revealed a selective induction of SDF1a, VEGF, and eNOS. In mice, SDF1a mimicked the protective 1, 25-VitD3 effect. In patients, high VitD3 levels were associated with a significant higher rate of favorable outcome, prospectively. CVS severity was inversely correlated with the VitD level. Patients with severe CVS exhibited attenuated expression of SDF1a on myeloid cells. CONCLUSION: 1, 25-VitD3 attenuates CVS after SAH. VitD chould be tested as potential treatment option to prevent CVS after SAH.